Greenhouse gas emissions reduction potential by increasing aquatic food consumption in China - Yixin Chen; Feng Wu; Hui Zeng (npj Science of Food)
Abstract Aquatic food production plays a crucial role in ensuring global food security, improving the quality of life, and reducing greenhouse gas (GHG) emissions. In this study, we have comprehensively evaluated the GHG emissions associated with China’s fisheries, considering both production and consumption. Scenario analysis was used to compare the potential of GHG emissions reduction under two conditions: maintaining current protein intake levels, and increasing the consumption of aquatic foods to align with global average. Our findings reveal that in 2020, the total GHG emissions from aquatic foods in China reached approximately 64.51 million tonnes CO2e (45.69 kg CO2e/per capita). However, when calculated from the consumption side, emissions amounted to just 19.32 million tonnes CO2e (13.69 kg CO2e/per capita). Increasing the consumption of aquatic foods could reduce GHG emissions by 24.55 million tonnes CO2e (17.39 kg CO2e/per capita). Effective strategies to achieve these reductions include minimizing waste in production and consumption, modifying dietary habits, and substituting terrestrial animal meat with aquatic foods.